PENGAMANAN SUARA DALAM VIDEO FORMAT 3GP DENGAN MENGGUNAKAN ALGORITMA ELGAMAL DAN STEGANOGRAFI DENGAN METODE LSB (LEAST SIGNIFICANT BIT) - Widhi Wirawan, I Made; Muliawan, I Wayan (Jurnal Ilmu Komputer; Vol. 4, No. 2 September 2011, 2011)
Security at the time information transmitted through the delivery of voice messaging becomes an important thing to do. Methods of cryptography and steganography become one of the options in safeguards toavoid if the attack on the voice message which can result in messages received by aperson not entitled to know the information. Cryptography requires a private key and public key for data encryption. While steganography requires two properties of the container receptacle and dataconfidential. Objects in this study is a video File Third Generation Project, which will be inserted with a voice message encrypted MPEG Layer 3. Cryptographic algorithms are performed using ElGamal and steganography using Least Significant Bit. ElGamal cryptographyrequires a private key and public key 3 pieces (prime, alpha, beta) to perform the encryption process. At Least Significant Bit method, a bit late on the video data will be replaced with a bit of the encrypted voice messages. Once replaced, the data will be anew video file. Securing the voice in the video Third Generation Project using ElGamal cryptography and steganography algorithms with the Least Significant Bit method can provide safety messages to minimize the possibility of unreadable messages hidden voice in the video
Keywords: Kriptography, Steganography, ElGamal, Least Significant Bit, Third Generation Project , Mpeg Layer 3